THE INFLUENCE OF WORK EXPERIENCE AND WORK ENVIRONMENT ON EMPLOYEE PRODUCTIVITY WITH ORGANIZATIONAL CULTURE AS AN INTERVENING VARIABLE AT PT BAHAGIA JAYA SEJAHTERA BOGOR - Palahudin Palahudin; Ismartaya Ismartaya; Dian Tri Nurhalisza (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study aims to examine the effects of work experience and work environment on employee productivity, with organizational culture serving as a mediating variable. A quantitative approach was employed using descriptive and path analysis methods. Data were collected through questionnaires distributed to 80 employees, representing the entire population, and selected using a saturation sampling technique. The research instruments were tested for validity and reliability and met the required classical assumption criteria. The Sobel test was applied to evaluate indirect effects. The findings indicate that: (1) work experience and work environment significantly influence organizational culture; (2) work experience, work environment, and organizational culture each have a direct and significant effect on employee productivity; and (3) work experience and work environment also exert an indirect effect on employee productivity through organizational culture. These results highlight the importance of fostering a supportive work environment and leveraging employee experience to strengthen organizational culture and enhance productivity. Keywords: Work Experience; Work Environment;Organizational Culture; Employee Productivity